Transforming Undergraduate Chemistry: A Decade of Flipped Classroom Innovations (2013-2023) (Foro de Educacion, 2025)
The flipped classrooms have been studied across a wide range of educational disciplines, but its use in undergraduate chemistry education is still not yet fully understood. This study addresses this issue by providing an in-depth review of how flipped classrooms are implemented within, and impact on, undergraduate chemistry courses. This review analyses the influence and effectiveness of flipped classroom as used in undergraduate chemistry education from 2013 to 2023. We follow the systematic review guidelines (PRISMA) to assess (30 studies) that looked at various aspects of flipped classrooms; including theoretical frameworks, technology, research methodologies, data collection and analysis, pre-class and in-class activities, and educational outcomes. Findings show that flipped classrooms, predominantly used theoretical frameworks, focusing on cognitive load theory, social constructivism, and self-determination theory. Editing videos and using content management systems were also commonly explored. Most studies used quasi-experimental methods, with many of the studies used hybrid methods of research. Data collection and analysis predominantly relied on quizzes, questionnaires, and qualitative analysis. Pre-class students watched videos and completed quizzes, while in-class activities included cooperative group discussion and problem-solving to promote active learning and greater learning outcomes. Overall, flipped classrooms provided benefits for undergraduate chemistry education, as it tended to improve academic performance, and or student engagement, and or comprehension and or group work skills. The pedagogical approach also attempted to reduce the performance gap between students. A systematic review of the literature and analysis demonstrate how the practice of flipped classrooms demonstrates theory and practice, and the use of educational technology to further support the pedagogical principles. A comprehensive review of flipped classrooms in undergraduate chemistry education has been established, and potential future directions have been articulated. The results of this review not only support educators, and policymakers, to create policy that is effective to promote education reform, but also to reimagine education and evaluation of potential.